A new species of Anchistrotos (Copepoda: Taeniacanthidae) from hilsa shad, Tenualosa ilisha (Actinopterygii: Clupeidae), off Iraq - Maran, Venmathi B A; Moon, Seong Yong; Adday, Thamir Katea (Folia parasitologica, 2014)
A new species of parasitic copepod Anchistrotos tangi sp. n. (Cyclopoida: Taeniacanthidae) is described based on adult female specimens collected from the gills of hilsa shad, Tenualosa ilisha (Hamilton, 1822) (Actinopterygii: Clupeidae) captured off Iraq. The new species differs from its congeners by having the following combination of characters in the adult female: 1) the rostral area sclerotised; 2) the presence of row of spinules on the proximal and distal margins of the anal somite; 3) the maxilliped claw with 2 long whip-like setae just crossing the distal edge of claw with serrated terminal margin; and 4) the leg 5 ornamented with patched spinules distally. This is the ninth nominal species of Anchistrotos Brian, 1906.
Keywords: Copepoda; žábry; Fish Diseases; Fishes; ženské pohlaví; zvířata; ryby; Female; nemoci ryb; infestace ektoparazity; Gills; Ectoparasitic Infestations; Indický oceán; Indian Ocean; Animals